A Case Analysis to Improve the Application Maintenance and Support Outsourcing of a National Airline - Chew, Alice (2009)
The reliance on outsourcing as a means of providing IT services has been growing steadily over the past decade. There have been numerous academic articles dedicated to IT outsourcing in general. This research seeks to fill the gap by providing insights to a less explored scope of IT activity outsourced - application maintenance and support (AMS); specifically, the post-contract management of AMS outsourcing. It is during this building block of management that success is ultimately determined.